EFFECT OF WASTE DREGS SUGARCANE COMPOST ON GROWTH AND RESULTS OF RED SPINACH IN PODSOLIC - rinny mariani (Jurnal Sains Pertanian Equator, 2018)
This study aims to determine the best dose of waste dregssugarcane compost on growth and yield of red spinach inpodsolic soil (Pod Soil) . This research was conducted at the agriculture faculty experimental field Tanjungpura University from 5th November 2012 to 5th March 2013, the experimental pattern using a complete randomized design (CRD) consist of 6 treatments and 4 replications, each replication consist of 4 plants so that there are 96 sample plants . The treatment are p0 ( without additionsugarcane waste dregs compost) , p1 ( 699 g / polybag equal as addition 7 % organic matter ) , p2 ( 1019 g / polybag equal to addition of 9 % organic matter ), p3 ( 1339 g / polybag equivalent to addition 11 % organic matter ) , p4 ( 1659 g / polybag equivalent to the addition of 13 % organic ingredients ) , and p5 (1979 g / polybag equivalent to addition 15 % organic matter) . Observed variableare the number of leaves (leaf) , plant height (cm) , fresh plant weight ( g ) , dry plant weight ( g ) , and root volume ( ml ) . the results showed that addition of sugarcane waste dregs compost dose at 1339 g / polybag equal to 11 % addition organic matter have significant effect onplant height , number of leaves , fresh plant weight , dry plant weight and root volume.